Physicochemical characterization of 5-Decyloxy-2-[[[4-Hexyloxyphenyl]Imino]Methyl]Phenol liquid crystal by inverse gas chromatography - Cakar, F.; Yazici, O.; Eran, B. Bilgin; Cankurtaran, O.; Karaman, F. (NATL INST OPTOELECTRONICS, 2008)
Trace amount of solvents such as benzene, toluene, ethylbenzene, n-propylbenzene, isopropylbenzene and chlorobenzene were passed through the gas chromatography column loaded with a new synthesized and characterized liquid crystal compound, 5-decyloxy-2-[[[4-hexyloxyphenyl]imino]methyl]phenol (DHOPIMP) which is coated on Chromosorb W. The retention diagrams of the solvents on the liquid crystal were plotted by means of specific retention volumes, V-g degrees at temperatures between 130 and 150 degrees C by inverse gas chromatography. The weight fraction activity coefficient at infinite dilution of the solvents, Omega infinity(1), the liquid crystal-solvent interaction parameters of Flory-Huggins, chi(infinity)(12), and equation of state, chi*(12) and effective exchange energy parameter, X-eff, were obtained. In addition, the partial molar heats of sorption, Delta(H) over bar (1,sorp) and mixing, Delta(H) over bar (infinity)(1) were determined. Phase transition temperatures of DHOPIMP were determined by polarizing microscopy and differential scanning calorimetry.
Keywords: Inverse gas chromatography; Liquid crystal; Phase transition temperature; Thermodynamics; Interaction parameter; COMPLEXES; POLYMER; IMINES; ALKOXY; Materials Science; Optics